1998
DOI: 10.1088/0953-8984/10/8/011
|View full text |Cite
|
Sign up to set email alerts
|

A TEM and neutron diffraction study of the local structure in the rhombohedral phase of lead zirconate titanate

Abstract: Transmission electron microscopy and neutron diffraction have been used to characterize ceramics and single crystals from the rhombohedral region of the (x = 0.06-0.45) phase diagram. Electron diffraction patterns showed the existence of superlattice reflections of the type , where h = k = l, and , which are not observed by neutron powder diffraction. The analysis of these reflections also revealed satellite spots around the , which are associated with periodic antiphase boundaries. The origin of these superl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
68
0
9

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 14 publications
12
68
0
9
Order By: Relevance
“…Here electron, but not neutron or x-ray, diffraction experiments reveal superlattice peaks incompatible with the R structure, variously attributed to rotations of the O octahedra [7,8] or to antiferroelectric-like cation displacements away from the average 111 direction [9,10].…”
Section: Introductionmentioning
confidence: 83%
“…Here electron, but not neutron or x-ray, diffraction experiments reveal superlattice peaks incompatible with the R structure, variously attributed to rotations of the O octahedra [7,8] or to antiferroelectric-like cation displacements away from the average 111 direction [9,10].…”
Section: Introductionmentioning
confidence: 83%
“…There are two controversial explanations for the existence of the incommensurate phase observed in the experiment. Ricote et al [4] concluded that the appearance of the IC phase is due to the surface effect by two experiments using the powder neutron diffraction and a transmission electron microscope. On the other hand, Viehland et al [5] considered it a bulk effect by directly observing the high resolution image of a transmission electron microscope.…”
Section: Discussionmentioning
confidence: 99%
“…The structural origin for these superlattice reflections is still under debate. 2,[5][6][7]9,21 However, the present in situ TEM study provides valuable insight into the physics mechanism for the presence of these superlattice reflections. It is clear in Fig.…”
mentioning
confidence: 99%